2016
DOI: 10.4103/2303-9027.175877
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic ultrasound-guided fine needle aspiration: The wet suction technique

Abstract: Endoscopic ultrasound-guided fine needle aspiration (EUS-FNA) has become a fundamental tool in obtaining cytopathological diagnosis of pancreatic tumors. When sampling solid lesions of the pancreas, the endosonographer can use two suction techniques to enhance tissue acquisition; the dry and the wet suction techniques. The standard dry suction technique relies on applying negative pressure suction on the proximal end of the needle after the stylet is removed with a pre-vacuum syringe. The wet suction technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 9 publications
0
32
0
7
Order By: Relevance
“…CEA levels are usually but not always low (< 20 ng/mL). In the majority of cases, aspirated fluid will be hypocellular with few groups of bland cuboidal epithelial cells embedded in granular debris[ 64 - 67 ]. Round to cuboid serous epithelial cells with clear cytoplasma and small, round nuclei forming loose clusters or monolayered sheets are identified in only 20%-25% of cases[ 64 , 66 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…CEA levels are usually but not always low (< 20 ng/mL). In the majority of cases, aspirated fluid will be hypocellular with few groups of bland cuboidal epithelial cells embedded in granular debris[ 64 - 67 ]. Round to cuboid serous epithelial cells with clear cytoplasma and small, round nuclei forming loose clusters or monolayered sheets are identified in only 20%-25% of cases[ 64 , 66 , 68 ].…”
Section: Discussionmentioning
confidence: 99%
“…Whether the application of suction during EUS-guided tissue acquisition could have contributed to the overall results was not evaluated in the current study. However, previous studies published in the literature have shown that the application of suction does not affect the diagnostic accuracy but is associated with bloody contamination of the specimens[ 26 - 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 29 ] found that when EUS-FNA was performed using the “wet suction” technique, in which the puncture needle is filled with saline solution, good quantities of better-quality specimens could be acquired compared with the conventional method, whereas Villa et al . [ 30 ] reported that not only were specimens of better quality but also diagnostic yield for the wet suction technique was significantly better at 85.5% compared with 75.2% for the conventional method ( P < 0.035). Nakai et al .…”
Section: Adaptations Of Puncture and Specimen Acquisition Methodsmentioning
confidence: 99%